Novel Synthetic Procedures in Organocatalysis - Petruzziello, Diego <1984> (Alma Mater Studiorum - Università di Bologna, 2013)

(untitled)
The main aim of my PhD project was the design and the synthesis of new pyrrolidine organocatalysts. New effective ferrocenyl pyrrolidine catalysts, active in benchmark organocatalytic reactions, has been developed. The ferrocenyl moiety, in combination with simple ethyl chains, is capable of fixing the enamine conformation addressing the approach trajectory of the nucleophile in the reaction. The results obtained represent an interesting proof-of-concept, showing for the first time the remarkable effectiveness of the ferrocenyl moiety in providing enantioselectivity through conformational selection. This approach could be viably employed in the rational design of ligands for metal or organocatalysts. Other hindered secondary amines has been prepared from alkylation of acyclic chiral nitroderivatives with alcohols in a highly diastereoselective fashion, giving access to functionalized, useful organocatalytic chiral pyrrolidines. A family of new pyrrolidines bearing sterogenic centers and functional groups can be readily accessible by this methodology. The second purpose of the project was to study in deep the reactivity of stabilized carbocations in new metal-free and organocatalytic reactions. By taking advantage of the results from the kinetic studies described by Mayr, a simple and effective procedure for the direct formylation of aryltetrafluoroborate salts, has been development. The coupling of a range of aryl- and heteroaryl- trifluoroborate salts with 1,3-benzodithiolylium tetrafluoroborate, has been attempted in moderate to good yields. Finally, a simple and general methodology for the enamine-mediated enantioselective α-alkylation of α-substituted aldehydes with 1,3-benzodithiolylium tetrafluoroborate has been reported. The introduction of the benzodithiole moiety permit the installation of different functional groups due to its chameleonic behaviour.